Manajemen Sekolah Ramah Anak: Studi Kasus di MTsN 6 Jombang - Akbarurrahman (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
Abstrac: Child-friendly school is a program that consciously strives to ensure the rights of children and protection for children from all aspects of life in an implemented and responsible manner. Likewise, in the learning process, it is required that the delivery of learning must be supported by good management and based on child- friendly principles, so that create a su a there environment schools, and classrooms that are conducive to students. Therefore, in this discussion, this researcher discusses friendly school management at Mtsn 6 Jombang. The aims of this research are, 1. To find out the shape of friendly school policies at Mtsn 6 Jombang, 2. To find out the implementation of child-friendly school management at Mtsn 6 Jombang. Researchers used a qualitative approach with the type of case study research with data collection techniques such as observation, interviews, documentation. Data analysis with three stages, the first stage is data reduction, data presentation, and verification. Based on the results of the study, it was found that 1. The form of policies applied in the process of implementing child-friendly school management at Mtsn 6 Jombang was based on the four pillars of child-friendly school principles, namely non-violence, discrimination, best interests for children's growth, and respect for children. 2. Implementation of child-friendly school management begins with the planning stage and analysis of situations and conditions, organizing and forming teams, implementing programs, and evaluating programs.